Factores del merchandising digital que inciden en la compra electronica de indumentaria y calzado (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
The competitive performance of companies is based on the decisions they make in the strategic and operational field, in commercial, financial, administrative, and operational aspects, among others. The objective of the article is to analyze the influence of digital merchandising factors, used by organizations, in the purchase of clothing and footwear. For this, a review of the literature on the subject and exploratory and descriptive research have been carried out. Although there is much research on the importance of using merchandising techniques to improve business productivity and profitability, little has been explored on its importance in digital formats. Within this framework, the article provides a set of digital merchandising factors that must be taken into account by organizations. As part of the work, a survey was carried out on Smartphone users with Internet access, to evaluate the importance of the factors surveyed in their purchasing behavior. Based on this analysis, companies will be able to design or redefine their digital merchandising strategy in light of the importance of the factors analyzed.
Keywords: merchandising, digital merchandising, purchasing behavior, e-commerce, digital channel